RISK FACTORS FOR THE DEVELOPMENT OF ADHESIVE PROCESS OF THE PELVIC ORGANS IN WOMEN OF REPRODUCTIVE AGE - Solieva U.Kh; Saidjalilova D.D; Khodjaeva D.N; Ayupova D.A (Scholar Express Journals, 2023)
The article discusses the risk factors for the development of adhesions of the pelvic organs in women of reproductive age.
Keywords: adhesive process; adhesiolysis; pathology